2015
DOI: 10.1017/s1751731114002274
|View full text |Cite
|
Sign up to set email alerts
|

The corpora lutea proangiogenic state of VEGF system components is turned to antiangiogenic at the later phase of the oestrous cycle in cows

Abstract: Blood vessel expansion and reduction in the corpus luteum (CL) is regulated by the vascular endothelial growth factor (VEGF) system and linked to the maintenance of the CL. The VEGF system has both angiogenic and antiangiogenic ligands and receptors. Our objective was to evaluate the relationship between the mRNA expression of angiogenic and antiangiogenic members of the VEGF system in the CL, throughout the luteal phase of the oestrous cycle in cows. The CL of 18 cows were collected by transvaginal surgery on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
8
0
3
Order By: Relevance
“…VEGFA is a potent mitogen that promotes the growth, migration and permeability of vascular endothelial cells in CLs throughout the luteal phase (Robinson et al 2007). Levels of this protein within the CL peak at around day 15 of the oestrous cycle but decline on luteolysis as witnessed in this study (Table 5) and by Guzmán et al (2015). This latter study also demonstrated that there are both pro-and anti-angiogenic isoforms of VEGFA in the bovine CL, and that immediately before luteolysis, there is an increase in anti-angiogenic isoforms.…”
Section: Molecular Basis Of Luteal Support and Steroidogenesissupporting
confidence: 82%
See 1 more Smart Citation
“…VEGFA is a potent mitogen that promotes the growth, migration and permeability of vascular endothelial cells in CLs throughout the luteal phase (Robinson et al 2007). Levels of this protein within the CL peak at around day 15 of the oestrous cycle but decline on luteolysis as witnessed in this study (Table 5) and by Guzmán et al (2015). This latter study also demonstrated that there are both pro-and anti-angiogenic isoforms of VEGFA in the bovine CL, and that immediately before luteolysis, there is an increase in anti-angiogenic isoforms.…”
Section: Molecular Basis Of Luteal Support and Steroidogenesissupporting
confidence: 82%
“…This latter study also demonstrated that there are both pro-and anti-angiogenic isoforms of VEGFA in the bovine CL, and that immediately before luteolysis, there is an increase in anti-angiogenic isoforms. With respect to the various isoforms identified by Guzmán et al (2015), we can deduce from the primers designed for this study that we amplified the single isoform 205, which has only been described as pro-angiogenic. Increased expression of this isoform in group A CLs, relative to group B and C CLs, further serves to confirm their viability.…”
Section: Molecular Basis Of Luteal Support and Steroidogenesismentioning
confidence: 99%
“…This is interesting, as Yamamoto, Rundqvist, Branco, and Johnson () determined that VEGF164 was the most potent VEGF isoform to reduce apoptosis and stimulate cell migration and proliferation. In agreement with the above, we previously found that the bovine corpus luteum expressed VEGF164a during development, but had no expression for VEGF164b (Guzmán et al, ). Therefore, the lack of expression of VEGF164b indicates that the mechanism that regulates the biological actions of VEGFxxx ligands in the bovine ovary is different from that observed in the murine and human tissues.…”
Section: Discussionsupporting
confidence: 88%
“…Transgenic mice, overexpressing VEGF165b in the ovary show lower fertility and increased follicle atresia (Qiu et al, ). Similarly, in the bovine corpus luteum, the expression of mRNA for VEGF120a is higher than that for VEGF120b during its development and this relationship was inverted before luteolysis (Guzmán, Macías‐Valencia, Fierro‐Fierro, Gutiérrez, & Rosales‐Torres, ). These results indicate that a balance between angiogenic and antiangiogenic isoforms is needed for normal follicle and corpus luteum development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation